COGNITIVE LINGUISTICS AND THEORETICAL PROBLEMS OF TRANSLATION - I.A.Egamberdiyeva (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation. Nowadays, a new linguocognitive approach is laying its foundation in the field of translation studies, and it is widely applied to the science. Linguistics of translation, which is considered a new direction of comparative linguistics, studies the activity of the translator in the translation of the original text. Linvocognitology of translation is not only cognitive sciences, but also closely related to linvoculturology, which studies the social character of language and its role in the life of society. The aim of this article is to showcase cognitive linguistics, theoretical problems of translation and development of modern translation theory and directions in it, basic principles of translation, ways of solving translation problems in the linguistic point of view.